Assessment of Customer Satisfaction with Quality of Services Provided in Maternity Ward of Shahid Sayyad Shirazi Hospital in Gorgan, Iran - Parvin Vizvari; Maryam Moradi; Leila Asadi (Golestan University Of Medical Sciences, 2018)
Background and objectives: Identifying gaps in the quality of services provided by medical centers can be useful for developing healthcare quality improvement plans. The purpose of this study was to assess satisfaction of clients with the quality of services in a maternity ward using the SERVQUAL model.  methods: This descriptive-analytical study was conducted on 175 women hospitalized in the maternity ward of Shahid Sayyad Shirazi Hospital in Gorgan, Iran. Data were collected using a demographic information questionnaire and a standard SERVQUAL questionnaire comprising 22 questions on service quality in five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The questionnaire was completed at the time of admission and after receiving the services to measure expectations and perceptions, respectively. The data were analyzed with SPSS (version 16) using paired sample t-test. Results: Most subjects were homemaker (92.35%) and pregnant for the first time (44.12%), and had high school diploma (43.53%). The level of expectations and perceptions in all dimensions was significantly higher than average (P=0.00009). There were significant negative gaps between the subjects' expectations and perceptions in all dimensions of service quality (P=0.00009).   Conclusions: The negative gap in the dimensions of service quality indicates the high-level expectations of clients in the maternity ward. Based on the clients' perceptions, their satisfaction was below their expectations after receiving the services, which created a negative gap. The high expectations of clients can be attributed to the raise in awareness of the community towards provision of health services and improvement of the healthcare system. Thus, the quality of the services provided and equipment used in hospitals should be high enough to meet the expectations of clients to a reasonable degree.